Development Handout about Bambusa vulgaris Population Structure in the Lake Sari Embun Region, Kalimantan Selatan as Supporting the Plant Ecology Course Material - Maidah Nazilah; Sri Amintarti; Dharmono Dharmono (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2024)
Learning activities can not be separated from the involvement of teaching materials, the use of teaching materials is one effort to create meaningful and quality learning. The students' environment and the surrounding area are rich in local potential, especially the diversity of animal and plant species. This potential can be used as an alternative to support the learning process. Plant population structure is the composition of plant populations that exist in a place. The Yellow Bamboo Plant has the potential to be a source of learning, so the results of the population structure study were made in the form of a locally based handout. The aim of this research is to determine the population structure of Yellow Bamboo (Bambusa vulgaris) in the Danau Sari Embun area, Tanah Laut Regency and to determine the suitability of Bambusa vulgaris population structure handout in the Danau Sari Embun area, Tanah Laut Regency as supporting material for Plant Ecology courses . The method used is the research and development method of the 5 phase Plomp model. The research results show that the population structure of Bambusa vulgaris in the Danau Sari Embun area shows that the Bambusa vulgaris population is in critical condition. The handout regarding the population structure of Bambusa vulgaris was declared very valid, while the readability test by students obtained very good criteria. It can be concluded that the Handout regarding the population structure of Bambusa vulgaris is worthy of being used as teaching material.